Răspuns :
Răspuns:
x₁ = (-1-√5)/2 ; x₂ = (-1+√5)/2
Explicație pas cu pas:
x² + x - 1 = 0
Notam :
a = 1 ; b = 1 ; c = -1
Δ = b²-4ac = 1²-4·1·(-1) = 1+4 = 5
√Δ = √5
x₁,₂ = (-b±√Δ)/2a
x₁,₂ = (-1±√5)/2
x₁ = (-1-√5)/2 ; x₂ = (-1+√5)/2
Răspuns:
[tex] {x}^{2} + x - 1 = 0[/tex]
[tex]x = \frac{ - 1 + - \sqrt{1 {}^{2} - 4 \times 1 \times ( - 1) } }{2 \times 1} [/tex]
[tex]x = \frac{ - 1 + - \sqrt{ 1 + 4} }{2} [/tex]
[tex]x = \frac{ - 1 + - \sqrt{5} }{2} [/tex]
[tex]x1 = \frac{ - 1 - \sqrt{5} }{2} [/tex]
[tex]x2 = \frac{ - 1 + \sqrt{5} }{2} [/tex]